2020
DOI: 10.1111/codi.15400
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopist factors associated with post‐colonoscopy colorectal cancer in a population‐based sample

Abstract: Aim: Factors associated with verified post-colonoscopy colorectal cancers (PCCRC) have not been well defined and survival for these patients is not well described. We aimed to assess the association of patient, tumour and endoscopist characteristics with PCCRC. Methods: Using population-based data, we identified individuals diagnosed with CRC from 1 January 2000 to 31 December 2005 who underwent a colonoscopy within 3 years prior to diagnosis. Detected cancers were those diagnosed ≤6 months following colonosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
6
2
1
Order By: Relevance
“…Like in the study carried out by Mlakar et al in 2018 in Slovenia [25] our results did not show statistically significant differences either according to age, sex, location of the tumour or deprivation index among the two types of PCCRC detected. With regard to the location of the CRC, the results of our study differ from those of Dossa et al due to the fact that although a higher frequency of CRC in distal colon was observed (38% and 37.2%) in both interval type and non-interval type PCCRCs in our study, they observed that the majority of cases were located in the proximal colon (54.2% of 367 PCCRCs) [26]. However, it should be noted that these studies included persons with symptoms with previous pathologies such as inflammatory bowel disease, hereditary syndromes, previous CRC, polyposis or diverticulosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Like in the study carried out by Mlakar et al in 2018 in Slovenia [25] our results did not show statistically significant differences either according to age, sex, location of the tumour or deprivation index among the two types of PCCRC detected. With regard to the location of the CRC, the results of our study differ from those of Dossa et al due to the fact that although a higher frequency of CRC in distal colon was observed (38% and 37.2%) in both interval type and non-interval type PCCRCs in our study, they observed that the majority of cases were located in the proximal colon (54.2% of 367 PCCRCs) [26]. However, it should be noted that these studies included persons with symptoms with previous pathologies such as inflammatory bowel disease, hereditary syndromes, previous CRC, polyposis or diverticulosis.…”
Section: Discussioncontrasting
confidence: 99%
“…We thank Spychalski et al for their comments on our recent study evaluating factors associated with the development of postcolonoscopy colorectal cancer (PCCRC) [1]. In this study of 367 patients with confirmed PCCRC and 412 patients with confirmed detected colorectal cancer (CRC) we showed that patient age and tumour location were most strongly associated with PCCRC and that endoscopist‐associated quality metrics that could be derived from an administrative dataset were not significantly associated with PCCRC.…”
mentioning
confidence: 70%
“…Our survival analyses indicated that PCCRC was associated with poorer one-year and one-to ve-year survival than dCRC. Despite some con icting results, the majority of previous studies found no difference in the prognosis for patients with dCRC and PCCRC (2,(26)(27)(28)(29)(30)(31). These studies have led to the interpretation of PCCRC as CRC arising mainly from missed or insu ciently resected precursor lesions.…”
Section: Discussionmentioning
confidence: 99%